Empowering Elementary Science Learning Through Articulate Storyline 3-Based Interactive Digital Media - Gani, Resyi Abdul; Windiyani, Tustiyana (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2025)
Development of Interactive Learning Media Using Articulate Storyline Three in the learning of social studies landscape materials aims to strengthen the learning of social studies the development and feasibility of a product development through interactive learning media. The research methodology used was the ADDIE (Analyze, Design, Development, Implementation, Evaluation) approach with the research subjects of grade IV-B SDN Julang Bogor City, the instruments used were validation sheets of media experts, linguists and subject matter experts with a total of three experts, student response instruments and teacher responses, and pre-test and post-test instruments. The validation results produced an average of 94% with the criterion of